Effects of high pressure on microstructure evolution and crystallization mechanisms during solidification of nickel. (7th March 2018) - Zhang, Hai-Tao; Mo, Yun-Fei; Liu, Rang-Su; Tian, Ze-An; Liu, Hai-Rong; Hou, Zhao-Yang; Zhou, Li-Li; Liang, Yong-Chao; Peng, Ping
Abstract: To deeply understand the effects of high pressure on microstructural evolutions and crystallization mechanisms of liquid metal Ni during solidification process, MD simulation studies have been performed under 7 pressures of 0 ∼ 30 GPa, at cooling rate of 1.0 × 10 11 K s −1 . Adopting several microstructural analyzing methods, especially the cluster-type index method (CTIM-2) to analyze the local microstructures in the system. It is found that the pressure has important influence on the formation and evolution of microstructures, especially of the main basic clusters in the system. All the simulation systems are directly solidified into crystal structures, and the 1421, 1422, 1441 and 1661 bond-types, as well the FCC (12 0 0 0 12 0), HCP (12 0 0 0 6 6) and BCC (14 6 0 8 0 0) clusters play a key role in the microstructure transitions from liquid to crystal structures. The crystallization temperature T c is enhanced almost linearly with the increase of pressure. Highly interesting, it is found for the first time that there is an important phase transformation point from FCC to BCC structures between 20 ∼ 22.5 GPa during the solidification processes from the same initial liquid system at the same cooling rate. And the effect of increasing pressure is similar to that of decreasing cooling rate for the phase transformation of microstructures during solidification process of liquid metal Ni system, though they have different concrete effecting mechanisms.